Community-Based Islamic Education through Local Traditions: Internalising Religious Values in the Tong Gentong Practice during Maulid Nabi - Sa’idah, Nur Izzatis; Prasetiya, Benny; Sain, Zohaib Hassan (Journal of Islamic Education Research, 2026)
This study examines the Tong Gentong tradition during Maulid Nabi in Pohsangit Leres Village, Probolinggo, Indonesia, conceptualising it as community-based Islamic education embedded in local culture. It analyses the internalisation of religious values: “ikhlas” (sincerity), generosity, “syukr” (gratitude), “ukhuwah” (brotherhood), and “ta‘awun” (mutual cooperation) through social practices and elucidates pedagogical mechanism beyond formal institutions. This study employed interpretive qualitative ethnographic case study. Data from participatory observation, in-depth interviews with key community stakeholders, and field documentation were analysed using reflexive thematic analysis to identify value transmission patterns. The findings indicate that Tong Gentong operates as a living pedagogical system where values are internalised through exemplary conduct, habituation, and intergenerational participation rather than through formal instruction. The tradition creates a shared moral space where religious teachings are enacted through collective practices, enabling sustainable character formation within everyday community life. This study reframes local traditions as structured informal Islamic educational mechanisms, offering an empirically grounded model integrating faith, culture and solidarity-enabling communities and educators to leverage such traditions for sustainable religious value internalisation in non-formal curricula. This study expands Islamic education beyond schools by reframing traditions as informal pedagogical systems integrating faith, culture, and solidarity, also offering empirically grounded community-based moral learning model.